Chromoblastomycosis in Taiwan: A report of 30 cases and a review of the literature. (26th October 2017) - Yang, Ching-Sheng; Chen, Chun-Bing; Lee, Yung-Yi; Yang, Chih-Hsun; Chang, Ya-Ching; Chung, Wen-Hung; Lee, Hua-En; Hui, Rosaline Chung-Yee; Chuang, Ya-Hui; Hong, Hong-Shang; Sun, Pei-Lun
Abstract: Chromoblastomycosis (CBM) is an implantation mycosis characterized by the presence of pigmented muriform cells in tissue. CBM is endemic in Taiwan, but only three formal cases have been reported to date because of underreporting. To describe and update its epidemiologic features, we report a series of 30 cases between 2003 and 2016 at a single medical center. Patients were predominately male (2.75:1). The mean age of onset was 65.9 years, and disease duration ranged from 2 months to 20 years. Diabetes was the most common comorbidity, and extremities were the most frequent sites of involvement. The lesions presented as papuloplaque, verrucous, cicatricial, targetoid, or mixed types. The dermoscopic features were variable, including red dots, white vague areas, black globules, and sand-like patterns. Among 10 Fonsecaea isolates further identified by sequencing the ITS regions of ribosomal DNA, nine were F. monophora and one was F. nubica . All but one patient received either systemic antifungal agents, surgical excision, or both. Surgical excision achieved a higher complete remission rate than the other forms of treatment did.